Influência da adição de Co nas propriedades de catalisadores à base de Ni suportados em MgAl2O4 aplicados na reforma a vapor do ácido acético - Mizuno, Stefanie Caroline Mayumi (2016)
The steam reforming of acetic acid (SRAcH), a model compound of pyrolysis-oil, was studied over MgAl2O4-supported Co-Ni catalysts with different Co/Ni ratios, prepared by impregnation using the incipient wetness method. The catalysts were characterized by X-ray powder diffraction, temperature programmed reduction, temperature programmed desorption, and thermogravimetry. In the steam reforming reaction of AcH, both Ni and Co catalysts suffered partial oxidation due to contact with the reaction mixture. The ketonization reaction occurred on the MgAl2O4 support and the presence of Co or Ni changed the reaction pathway of species adsorbed on the support, which suppressed the formation of acetone. The cleavage of C-C bonds was favored on the Ni surface, resulting in CHx species, which in the presence of H2 were preferentially hydrogenated to CH4 at low temperatures. On the other hand, on the Co surface the CHx species were decomposed to C* and H* as the temperature increased. The addition of Co to Ni catalysts inhibited CH4 formation and carbon accumulation.